O uso da realidade aumentada e da retextualização: ressignificação dos processos de recepção, circulação e produção de textos - Coe, Geanne dos Santos Cabral (2019)
The research developed in this dissertation had as object of study the work with text production. In this sense, it was sought to invest efforts for a re-signification in the treatment given to this linguistic practice in the teaching-learning process. For this, the processes of retextualization and the resource of the Augmented Reality were articulated. It was hypothesized that this articulation could provide subsidies for the processes of reception, circulation and production of texts. Thus, the objective of the present work was to analyze the peculiarities of the processes of reception, circulation and production of texts effectuated through retextualization and socialized through Augmented Reality. Thus, for the purpose of accomplishing the proposed objective, a theoretical research was carried out on the trajectory of the teaching of text production over the years, from the perspective of the authors Red and Cordeiro (2011), Geraldi (2003), Antunes (2003), Guedes (2009), Bunzen (2007), among others. The main concepts for the work with digital genres in the classroom, such as multiletrations, multimodality, multisemioses, discussed by Dionísio and Vasconcelos (2013), Ribeiro (2017), Rojo e Barbosa (2017) and Kleiman, Ceniceros and Tinoco 2013). This research counted on the data collection from activities of text production, proposals to high school students. Several authors point out that the tendency of a text production teaching in the school is still based on a traditional conception, which can be restructured from the proposition of activities that consider the conditions of reception, circulation and production of texts. In this way, the practice of retextualization allied to Augmented Reality allows a motivation for the production of texts, in addition to providing effective reception and circulation of the texts produced. The combination of these three elements may represent an advance for the treatment of text production in school, since such elements - reception, circulation and production of texts - are approached in a dissociated way, which makes it impossible to recognize the subject / reader / author, of the different textual supports, of the operation of the multiple languages. The data of this research were obtained by means of retextualization activities and the use of Augmented Reality, proposed to high school students of a school in the rural area of the city of Lavras, in the interior of Minas Gerais, and demonstrated the potential to be explored in the production from a multisymnia perspective.